PVAR model with collapsed instruments in the real exchange rates misalignment's analysis - Joisp Arnerić; Antoni Šitum (Croatian Operational Research Review, 2022)
The causes and the consequences of the real exchange rates misalignment's of European Union (EU) members were examined in this paper by implementing stationary panel vector autoregression (PVAR) model with fixed effects. PVAR methodology was recognized as the most appropriate in line with data structure and the objectives of the research. For estimation purpose, the generalized method of moments (GMM) in first differences, with a reduced number of instruments, was applied. Primarily objective was to find whether a collapsed matrix of instruments helps in reducing the dynamic panel bias within the two--step estimation of PVAR model when employing the first difference GMM estimator. Even though, the benefits of collapsed instrument matrix have been documented in rare simulation studies, this paper empirically demonstrates it's utility considering balanced panel data. In that context, recommendations to potential users are given and supported by open source codes in the RStudio environment. Besides, auxiliary findings contribute to a better understanding of influential channels through which EU policy makers should reduce a real exchange rates misalignment's.